Professionally Created Content Related to HPV Vaccination on TikTok - Corey H. Basch; Grace C. Hillyer; Erin T. Jacques (Frontiers Media S.A., 2022)
Despite the protective abilities of the HPV vaccine, roughly half of adolescents in the United States have not completed the recommended HPV vaccine series. Professionals have taken to using social media platforms to encourage health behaviors such as receipt of the HPV vaccine. As such, the purpose of this study was to identify content created by professionals related to HPV on TikTok. This descriptive, cross-sectional study was conducted in January 2022 using the hashtag #HPV Vaccine to examine the 100 English language videos created by people who claimed to be health professionals. In addition to capturing metadata, each videos' content and subsequent comments were coded. Overall, 75.0% of the videos mentioned HPV-related cancer but few discussed vaccination as a cancer preventive measure (40.0%). More than half (52.0%) of the comments were neutral in tone and most focused on cancer (54.0%), alternative medicine (58.0%), and general questions about vaccination (62.0%). Comments about videos with greater numbers of "likes" more often mentioned cancer (85.0% vs. 46.3%, p = 0.002), the age at which to get vaccinated (70.0% vs. 41.3%, p = 0.02) and more frequently posed questions about vaccination (80.0% vs. 41.3%, p = 0.002) and cost and insurance coverage of vaccination (35.0% vs. 11.3%, p = 0.02) compared to videos with fewer "likes." The power of provider information is paramount with HPV vaccine uptake. As providers increasingly create health messages on platforms such as TikTok, it is important that they remain aware of the potential for opposing or non-factual discourse.